Measuring The Effectiveness of Merdeka Curriculum in Religious-Based Private Schools: A Case Study Of SMP Muhammadiyah 10 Bandung: Menakar Efektivitas Kurikulum Merdeka di Sekolah Swasta Berbasis Keagamaan: Studi Kasus SMP Muhammadiyah 10 Bandung - Ahmad Maulana; Jaky Hasbia Fikry; Suherlan, Moh. Azmie Maulidie (CV. Media Publikasi Profesional, 2024)
This study aims to analyse the implementation of Merdeka Curriculum at SMP Muhammadiyah 10 Bandung in order to improve the quality of student-centred learning, as well as identify the challenges teachers face in understanding and implementing the new curriculum structure. This research uses a qualitative approach with a literature review method and institutional documentation as the main data sources. The data analysis technique was carried out thematically on curriculum documents, teaching modules, and scientific literature related to Merdeka Curriculum. The results showed that schools have seriously implemented the principles of the Merdeka Curriculum, including through teacher training and learning communities, but technical errors were still found in the preparation of Learning Objectives and Learning Objective Flow. This finding confirms the importance of curriculum literacy at the implementing level so that learning can be designed systematically and effectively. The implications of this study include the need for continuous training policies for teachers and more intensive curriculum supervision, to ensure the success of the Merdeka Curriculum implementation as a whole. The originality of this research lies in highlighting the technical dynamics in the implementation of the independent curriculum at the junior high school level, which has rarely been discussed in previous studies.